2018
DOI: 10.1080/20013078.2018.1446660
|View full text |Cite
|
Sign up to set email alerts
|

Glycosylated extracellular vesicles released by glioblastoma cells are decorated by CCL18 allowing for cellular uptake via chemokine receptor CCR8

Abstract: Cancer cells release extracellular vesicles (EVs) that contain functional biomolecules such as RNA and proteins. EVs are transferred to recipient cancer cells and can promote tumour progression and therapy resistance. Through RNAi screening, we identified a novel EV uptake mechanism involving a triple interaction between the chemokine receptor CCR8 on the cells, glycans exposed on EVs and the soluble ligand CCL18. This ligand acts as bridging molecule, connecting EVs to cancer cells. We show that glioblastoma … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
74
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 69 publications
(75 citation statements)
references
References 108 publications
(143 reference statements)
1
74
0
Order By: Relevance
“…TEM images also confirmed the typical morphology of EVs (Figure 1(b,d)). Size distribution profiles, quantified by measuring the diameter of 100 at random‐selected EVs in eight TEM images (Figure 1(d,e,f)) and by nanoparticle tracking analysis (NTA, Figure 1(g)), were comparable to previously reported size of exosomes/small EVs (70–200 nm) isolated from glioblastoma culture media [2,4,9,57].…”
Section: Resultssupporting
confidence: 80%
See 2 more Smart Citations
“…TEM images also confirmed the typical morphology of EVs (Figure 1(b,d)). Size distribution profiles, quantified by measuring the diameter of 100 at random‐selected EVs in eight TEM images (Figure 1(d,e,f)) and by nanoparticle tracking analysis (NTA, Figure 1(g)), were comparable to previously reported size of exosomes/small EVs (70–200 nm) isolated from glioblastoma culture media [2,4,9,57].…”
Section: Resultssupporting
confidence: 80%
“…To circumvent the need for personalized neo‐antigen identification and peptide synthesis, we proposed that EVs may represent a more comprehensive, cell‐free, autologous source of neo‐antigens and tumour‐associated antigens, which could be targeted for efficient DC loading [3,35,67]. Since EVs can be internalized by recipient cells via glycan‐specific receptors [4–6], we profiled the surface glycosylation of glioblastoma cell line‐derived EVs and modified their glycosylation for enhanced internalization by DCs. By measuring lectin‐binding properties of EVs in both ELISA‐based assays and immunogold‐TEM, we showed that the surface glycoconjugates of our EV preparations were dominated by immune inhibitory sialic acid‐capped N ‐glycans and complex bi‐antennary glycans.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, this chemokine participates in the differentiation of immature dendritic cells into tumor-associated dendritic cells (TADC) [ 268 , 269 ]. Other functions of CCL18 in the tumor include participation in the intercellular communication dependent on extracellular vesicles [ 270 ]. This chemokine binds to glycosaminoglycans on extracellular vesicles, which allows them to be retained on cells with an expression of CCR8, a receptor for CCL18.…”
Section: Ccr8mentioning
confidence: 99%
“…Molecules exposed on the EV surface, including fibronectin, PS, and integrins, interact with heparan sulphate proteoglycans [86], T‐cell immunoglobulin‐ and mucin‐domain‐containing molecules [87], and cell‐associated extracellular matrix [8] present on recipient cells. Chemokines and their receptors may act as bridges linking the two membranes together, as they are expressed on both EVs and cells [88,89]. Although follicular dendritic cells do not express MHC‐II, their surface can become fully decorated with vesicles that do (likely derived from B‐cells) [90].…”
Section: Contact Uptake and Fusionmentioning
confidence: 99%